RE: Are Cross-Sectional Imaging Modalities Enough for Sarcopenia Assessment? - , Rasim Eren Cankurtaran, Yasin Celal Güneş, Emre Dirican, Oktay Algın, Damla Cankurtaran, Öykü Tayfur Yürekli (Turkish Journal of Gastroenterology 1, 2024)
Cite this article as: Cankurtaran RE, Güneş YC, Dirican E, Algın O, Cankurtaran D, Tayfur Yürekli Ö. RE: Are cross-sectional imaging modalities enough for sarcopenia assessment? Turk J Gastroenterol. 2024;35(1):75.